Mães más: um olhar sobre o abandono. - Lima, Auricéa Xavier de Souza (2011)
This research analyzes, from the cases of abandonment of babies propagated in the journalistic media in the period of 01/01/2008 to the 31/12/2010, questions related to the woman deserter of the maternity; to the feminine identity and its representation in the media; the discrimination of the women whom they appeal to the abandonment in the form as is boarded the news articles, as well as, to the abandonment situation where the same ones for times if find during the gestation. It discourses on the politics of protection to infancy and the question of the abandonment in the colonial period. It appeals to the research of Venâncio (2004) that it deals with detailed form very on the question of the abandonment in Brazil of the colonial period. Thus being, we perceive, as these cases of abandonment had had influence in what we can call the first politics for infancy and as this reality already has some centuries, are part of our history and continue so present in the current days. After that it deals with the relation between the journalistic media and the abandonment; of the results and analyses of the research, as well as, it analyzes some cases. It reflects on changes and conservations in the forms of the abandonment today in relation to the colonial period and analyzes the social reality of these women, whom, for diverse reasons, they appeal to the abandonment of babies. We conclude bringing for the quarrel new alternative suggested to decide the problem of the abandonment today, as it is the case of the anonymous childbirth. From this analysis, it considers a reflection on the responsibility of all the social actors in the act to generate and to create children in detriment of myths and concepts that throughout history have exclusively made responsible the women for the creation and reproduction human beings.